Learning Islamic Religious Education and Character at Elementary School Levels During the Pandemic - Nurul Fatonah; Nurdin Muhamad; Nuril Muwahidah Fadilah; Masripah , (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The research was conducted to examine the implementation of education on the pandemic of covid-19. Education is one of the sectors affected by the impact of the pandemic covid-19. Various media and the strategy were undertaken by teachers for students ' rights in education. Elementary School becomes the locus of interest by researchers to be studied. The purpose of this research is to conduct a study of the teachers and the ethics associated with the media and the strategies used by teachers in learning about the pandemic. It’s chosen IRE’s teacher and ethics in research is due to the Elementary teachers of subjects separate and different from the class teacher. This research uses qualitative research methods through a phenomenological approach. The location of this research was in an Elementary school in Garut Regency, selected samples in the snowball as many as 34 informant teachers. The subject in this study is teachers. This study shows that the need for innovation is done by teachers to ensure the sustainability of the learning process.